Specyfika kalkulacji kosztu wytworzenia produktu w zakładzie drobiarskim - Sobów, Elżbieta (Specific Cost Calculation of Product Manufactured in a Poultry Processing, 2007)
This article presents a poultry processing plant which accepted a chart of accounts with a document concerning the rules of accounting introducing necessary changes due to its owner's information requirements in order to control the cost in a plant and to make correct decisions. Due to the fact that the owner is an American company, some changes have their origin in the methodology of cost calculation of product manufactured according to American system. Adopting American methodology involves breaking by a plant with the way of cost calculation that is currently used in Poland by another plants of this business. The implementation of this methodology gives the possibility of reliable evaluation of products and lets us know on which groups of products a poultry processing plant earns a profit and on which it incurs a loss. Additionally, it protects a plant from false cost raising of by-products by overstated evaluation, and at the same time it protects from overstated evaluation of stocks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 459-470